Kolaborasi Kebaikan Lintas Elemen Masyarakat : Strategi Mewujudkan Masa Depan yang Gemilang Generasi Alpha TPQ Al Muttaqin - Wiranda, Aditya; Nurcahyani, Anggita; Rahayu, Asmi Lidya Pradipta; Khadijah, Khadijah; Wardana, Wisnu Ahmad; Wiyanti, Wiyanti; Alfarizi, Abdulloh; Mubarok, Luthfi Adli (State Islamic University of Mataram, 2025)
Collaboration has become a trend in people's lives and has beneficial value by maximizing the opportunity aspect. This community service activity uses the Participatory Action Research (PAR) approach by implementing a collaboration strategy that involves parents, synergizes with asatidzah, and gets support from religious leaders and the surrounding community. The stages of implementing the work program are planning, implementation, and evaluation. The results show that community service activities with this good collaboration strategy are running very well in realizing the alpha generation in TPQ education units.